Blended-Learning: The Responses from Non-English Students in the Indonesian Tertiary Context - Fatimah Mulya Sari; Achmad Yudi Wahyudin (Universitas Teknokrat Indonesia, 2019)
The process of language teaching and learning has undergone major changes due to the developments of technology. The use of technology in education field has paved the way for higher education institution to innovatively shape their modern media in a language teaching and learning. Subsequently, the implementation of blended-learning has aroused at the Universitas Teknokrat Indonesia for approximately one and a half year ago to maximize the use of technology. Most lecturers in all study programs have increasingly utilized the social network sites such as Instagram, Facebook, WhatsApp, etc. for the successfulness of blended-learning. This present study aims at exploring the students’ responses on how blended-learning might be used to develop their language learning and discovering their attitudes towards the implementation of blended-learning as an interactional teaching and learning tool in English for Business course. Employing a qualitative in form of a case study, eighty-two undergraduate students from study program of Informatics Engineering were observed, interviewed, and distributed questionnaires. The data were performed to collect the students’ responses and students’ attitudes toward the implementation of blended-learning in the process of their language learning. The findings were found out that most students from Informatics Engineering major showed their positive responses and positive attitudes using blended learning for the language teaching and learning. They also gained some educational benefits for their English language development. Thus, this blended learning brings us to the new trend for language teaching and learning media in order to motivate the students in enhancing their language acquisition.